2022
DOI: 10.3390/life12030421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucocorticoid Therapy on Sepsis Depend Both on the Dose of Steroids and on the Severity and Phase of the Animal Sepsis Model

Abstract: Steroids are currently being used in sepsis, particularly in septic shock. However, clinical trials to date have shown contradictory results. This could be attributed to the different patient endotypes and steroid doses, which have also contributed to the inconclusive results. We investigated the effects of glucocorticoid therapy on sepsis in a polymicrobial sepsis model in a variety of settings, such as steroid dose, severity, and sepsis phase. We used a rat model of fecal slurry polymicrobial sepsis. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…These results highlight the importance of rapid and accurate diagnosis of sepsis for the early initiation of corticosteroid therapy in order to improve treatment outcomes. The delayed initiation of corticosteroids (i.e., ≥4 to 6 h) after recognizing sepsis in previous studies might account for the reported harmful effects or lack of benefits associated with corticosteroid therapy [ 28 ]. However, rapid, accurate diagnosis of sepsis, especially in critically ill patients, is challenging because of the presence of inflammation associated with underlying non-infectious diseases, as well as slow confirmation of infection based on microbiological cultures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the importance of rapid and accurate diagnosis of sepsis for the early initiation of corticosteroid therapy in order to improve treatment outcomes. The delayed initiation of corticosteroids (i.e., ≥4 to 6 h) after recognizing sepsis in previous studies might account for the reported harmful effects or lack of benefits associated with corticosteroid therapy [ 28 ]. However, rapid, accurate diagnosis of sepsis, especially in critically ill patients, is challenging because of the presence of inflammation associated with underlying non-infectious diseases, as well as slow confirmation of infection based on microbiological cultures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ALT and creatinine levels in the plasma sample were determined by an automated chemistry analyzer (Beckman Coulter, Brea, CA, USA) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data regarding the potential increased risk of secondary infection or long‐term impact on performance in septic foals treated with glucocorticoids is lacking. Still, the variable effects of glucocorticoids on patient outcomes in human sepsis indicate the timing of their administration, the dose utilized and the stage and severity of disease when they are implemented is important when trying to harness the beneficial effects of glucocorticoids when treating sepsis (Park et al., 2022).…”
Section: Introductionmentioning
confidence: 99%